(untitled) (Pedagogy of Higher and Secondary Education, 2021)
The article studies the issue of theoretical and methodical basis of geography teaching in the profile school. Educational content’s structure as analysed. The analyse and monitoring conclusions on pedagogical experiment to find out the level geography knowledge of high school students are being revealed.